THE EFFECT OF USING AUGMENTED REALITY (AR)-BASED LAB GUIDES ON SCIENCE LITERACY AND STUDENT LEARNING INTEREST IN VIRUS MATERIAL IN GRADE X AT SMA NEGERI 3 REJANG LEBONG - Meti Herlina; Sela Anggi Monika; Apriza Fitriani (BioCONCETTA, 2025)
This study aims to determine the effect of augmented reality-based laboratory guidelines on students' science literacy and interest in learning. Two classes were involved as the experimental class and the control class with different treatments. The experimental class applied Augmented Reality-based laboratory guidelines, while the control class did not. The research sample was class X IPA 2 as the experimental class and class X IPA 3 as the control class. The instruments used were essay questions to measure literacy skills and questionnaires to measure learning interest. The results showed that there was a significant effect of Augmented Reality-based practicum guides on students' science literacy skills, with a sig value < alpha value, namely 0.000 < 0.05, or tcount > ttable, namely 4.161 > 2.010. In addition, there was also a significant effect on students' interest in learning, with a sig value < alpha value, namely 0.00 < 0.05 or tcount > ttable, namely 4.790 > 2.010.